2015
DOI: 10.1016/j.jascer.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Li4Ti5O12 electrode thin films by a mist CVD process with aqueous precursor solution

Abstract: a b s t r a c tSpinel Li 4 Ti 5 O 12 thin films were prepared by a mist CVD process, using an aqueous solution of lithium nitrate and a water-soluble titanium lactate complex as the source of Li and Ti, respectively. In this process, mist particles ultrasonically atomized from a source aqueous solution were transferred by nitrogen gas to a heating substrate to prepare thin films. Scanning electron microscopy observation showed that thin films obtained by this process were dense and smooth, and thin films with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…For instance, Tadanaga et al . reported a novel mist CVD method for the preparation of Li 4 Ti 5 O 12 thin film . Furthermore, Li 4 Ti 5 O 12 materials with the favorable carbon coating have been also synthesized via a CVD technique, and therefore a good electrochemical performance can be easily reached .…”
Section: Synthesis Methods Of Li4ti5o12mentioning
confidence: 99%
“…For instance, Tadanaga et al . reported a novel mist CVD method for the preparation of Li 4 Ti 5 O 12 thin film . Furthermore, Li 4 Ti 5 O 12 materials with the favorable carbon coating have been also synthesized via a CVD technique, and therefore a good electrochemical performance can be easily reached .…”
Section: Synthesis Methods Of Li4ti5o12mentioning
confidence: 99%
“…LTO thin films have been grown via PLD [346][347][348][349], sputtering [350,351], sol-gel [352,353] and CVD processes [354]. Deng et al [348] reported the growth of the ( 111)-oriented LTO thin films on Pt/Ti/SiO 2 /Si substrates via PLD, showing a discharge capacity of 157 mAh/g after 10 cycles with a constant current density of 10 µA/cm 2 .…”
Section: Anodesmentioning
confidence: 99%
“…Many deposition methods have been applied to synthesize Li 4 Ti 5 O 12 film anodes, including sol-gel [62,63], magnetron sputtering [64,65], spray pyrolysis [66], aerosol [67] and CVD [68].…”
Section: Anode Materialsmentioning
confidence: 99%